Restraining the Unitary Executive: A Regime Ethics Basis for Administrator Defiance of Presidential Directives. (3rd July 2020) - Cook, Brian J.
Abstract : The now dominant unitary executive model of presidential power claims historical, constitutional, and moral warrant for placing under direct presidential control all authority to interpret and execute the law. What are administrators to do when faced with presidential directives that they find legally distorted and morally wrong? Administrative ethics frameworks obligate administrators to exercise moral agency and fulfill their autonomous commitment to serve higher-order purposes in the form of the public interest. A substantive value conception of the public interest is dominant in these frameworks. This is problematic in liberal democracies, however, where end values are contested, and individuals are presumed to be the primary holders of purposes. An understanding of the public interest as concerned with the capacities and integrity of the constitutive institutions of the regime will involve administrators in constitutional politics and deliberation about the law on terms less threatening to liberal democratic norms. Such a regime ethics can thus provide administrators with a stronger ethical defense when they choose to defy presidential directives they find legally and morally defective.